2022
DOI: 10.1371/journal.pone.0264635
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian flow characteristics through different angled bends: Exploring the spatial variation of velocity

Abstract: Common geometrical layouts could potentially be bottlenecks, particularly during emergency and high density situations. When pedestrians are interacting with such complex geometrical settings, the congestion effect might not be uniform over the bottleneck area. This study uses the trajectory data collected through a controlled laboratory experiment to explore the spatial variation of speeds when a group of people navigates through bends. Four turning angles, i.e., 45°, 90°, 135° and 180°, with a straight corri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Thus, while comparing the different lanes (i.e., within the corridor), speed variation is affected mainly by the angle of the intersection rather than the speed at which the pedestrians are moving. The findings are in line with those of Hannun et al [43], who observed that the speed reduction is the lowest in the inner lanes for unidirectional flows in bends.…”
Section: Average Speed Profiles Along Corridorssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, while comparing the different lanes (i.e., within the corridor), speed variation is affected mainly by the angle of the intersection rather than the speed at which the pedestrians are moving. The findings are in line with those of Hannun et al [43], who observed that the speed reduction is the lowest in the inner lanes for unidirectional flows in bends.…”
Section: Average Speed Profiles Along Corridorssupporting
confidence: 93%
“…Moreover, it can be visualized that the congestion and resulting reduction in speed are severe in the inner corner of the intersection in all scenarios. The speed reduction for unidirectional flows is more severe in the corners, as reported by Hannun et al [43]. Thus, for both unidirectional flow through bends, as well as the bi-directional flow of pedestrians, the speed reduction is greater at the corners or bends.…”
Section: Spatial Distribution Of Average Instantaneous Speedssupporting
confidence: 66%
“…Although crowd barriers also formed at the curve and straight bottlenecks, they had less impact on pedestrian speed, and pedestrians still maintained a certain speed to pass through the bottleneck. To support our findings, we refer to the study conducted by Jamal Hannun and Charitha Dias, which investigated pedestrian velocity characteristics through different angled bends [30]. In Jamal's experiment, four turning angles (0 • , 45 • , 90 • , and 135 • ) were investigated, and the velocity varied significantly in the bending space at all angles except for the 0 • angle.…”
Section: Lateral Velocity Distributionsupporting
confidence: 62%
“…Due to factors such as space limitation, strong purposes, and so on in subways, pedestrians passing through bottlenecks often demonstrate velocity jump and path selection diversification based on individual characteristics, which are represented as individual speed, individual transit time, trajectory, and so on. Individual speed and individual transit times are frequently used to describe individual characteristics [17,25,30,31]. The total transit time and time gap are frequently used to describe group characteristics [12,22].…”
Section: Passing Time In Bottleneck Corridorsmentioning
confidence: 99%
“…So far, there are quite a few studies on angled corridors (Shi et al 2018 ). The current studies mainly explore the influences of the number of pedestrians on pedestrian movement behavioral characteristics in corridors with different angles (Rahman et al 2020 ; Chen et al 2019 ; Hannun et al 2022 ). Although scholars have conducted extensive research, the mechanisms regulating human walking are not fully understood.…”
Section: Introductionmentioning
confidence: 99%